1989
DOI: 10.1111/j.1445-5994.1989.tb00278.x
|View full text |Cite
|
Sign up to set email alerts
|

Allergic Fungal Sinusitis Presenting as a Paranasal Sinus Tumour

Abstract: Allergic fungal rhinosinusitis is a rare complication of atopic upper airways disease which may present initially as an expansive tumour of the paranasal sinuses. This reported case was caused by the rare fungal pathogen Bipolaris hawiiensis and illustrates typical clinical and laboratory features of this disorder. Although the optimum management of allergic fungal sinusitis is controversial, combined therapy with surgical clearance, antifungal agents and corticosteroids produced a favourable outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(51 citation statements)
references
References 8 publications
1
49
0
Order By: Relevance
“…Subsequent reports of phenotypically similar patients eventually led to the disease entity "allergic fungal rhinosinusitis" (AFRS). [357][358][359] Given its histopathologic similarity to allergic bronchopulmonary aspergillosis, AFRS was originally thought to represent a clinical manifestation of IgEmediated response to fungus within the nose and sinuses. 360 When Ponikau et al 361 later found that eosinophils and fungi could be recovered from essentially all patients with CRS, a broader role for noninvasive fungi in the pathogenesis of CRS with and without polyposis was considered.…”
Section: S55mentioning
confidence: 99%
“…Subsequent reports of phenotypically similar patients eventually led to the disease entity "allergic fungal rhinosinusitis" (AFRS). [357][358][359] Given its histopathologic similarity to allergic bronchopulmonary aspergillosis, AFRS was originally thought to represent a clinical manifestation of IgEmediated response to fungus within the nose and sinuses. 360 When Ponikau et al 361 later found that eosinophils and fungi could be recovered from essentially all patients with CRS, a broader role for noninvasive fungi in the pathogenesis of CRS with and without polyposis was considered.…”
Section: S55mentioning
confidence: 99%
“…Two years later, Katzenstein et al independently observed the pathophysiologic resemblance between allergic bronchopulmonary aspergillosis and 7 cases of chronic fungal sinusitis. The term allergic fungal sinusitis was coined in 1989 [3]. Since then, extensive work has been carried out to explain the disease as an immunologically mediated disorder (IgE mediated) rather than a precursor of invasive fungal disease [4][5][6][7] .…”
Section: Introductionmentioning
confidence: 99%
“…10 During the past several years, there has been an increase in the frequency of cases of phaeohyphomycosis caused by the members of the genera Bipolaris and Exserohilum. 11 Allergic phaeohyphomycosis caused by dematiaceous fungi, such as Alternaria, Bipolaris, Cladosporium, Curvularia, and Exserohilum species, are capable of localized colonization, and infection of the paranasal sinuses in both immunocompetent [3][4][5][6][7][8][9][11][12][13][14][15][16][17][18][19][20][21] and immunocompromised hosts. [21][22][23][24] Intracranial extension of the dematiaceous fungi in patients with allergic fungal sinusitis has been reported in the literature, 4,13,19,20 which illustrates how dangerous these fungi can become.…”
Section: Discussionmentioning
confidence: 99%
“…1 The disease is typically caused by a species of Aspergillus, 2 as well as numerous other genera and species of both dematiaceous and nondematiaceous fungi. [3][4][5][6][7][8][9] At the University of Texas Medical Branch, between 1989 and 1991, we treated six cases of fungal sinusitis that were caused by Bipolaris spicifera, Exserohilum rostratum, Curvularia verruculosa and Pseudallescheria boydii. Our experience, as well as that published in the literature, suggests that allergic fungal sinusitis is being recognized more frequently.…”
mentioning
confidence: 99%